A subspace-tracking approach to interference nulling for phased array-based radio telescopes. - Ellingson, S.W (IEEE Transactions on antennas and propagation)
Several next-generation radio telescopes, now in the planning stages, are based on phased-array technology. One reason for this is to make use of adaptive nulling techniques to combat radio frequency interference, which is a growing problem for radio astronomy. This paper presents a low-complexity approach to interference nulling which is suitable for use in such systems. The approach uses subspace-tracking to identify interference, followed by spatial projections to place deep nulls in the directions of interferers. This technique overcomes two limitations of power-minimization algorithms (e.g., "minimum variance"), namely power inversion and pattern rumble, which create serious problems for radio astronomy. Furthermore, this technique imposes a lower computational burden and provides side information which is useful in later stages of data processing. Performance results from a phased array demonstrator system and a simulation are presented